Ecologia comparada de formigas do gênero ectatomma no cerrado brasileiro - Neves, Nataly Mendes (2024)
Understanding the factors that allow the coexistence of multiple species in biological communities is a central question in ecology, and various mechanisms have been proposed to explain the maintenance of this diversity. One mechanism is niche partitioning, which predicts that, to avoid interspecific competition, species must differentiate in resource use to coexist. Therefore, in this study, we analyzed the three main niche dimensions (temporal, spatial, and trophic) of six Ectatomma ant species (E. permagnum, E. opaciventre, E. edentatum, E. planidens, E. tuberculatum, and E. brunneum) to understand the importance of resource partitioning for their coexistence, as phylogenetically related species (like those of the same genus) have more similar niche spaces, resulting in strong competition when these are overlapped. To investigate spatial variation, sampling was carried out in three vegetation types of the Cerrado (open savanna, dense savanna, and dry forest) using pitfall traps. To determine the temporal niche, pitfall traps were used in a way that they remained active for a 2-hour period: in the morning (06:00 - 08:00 am), in the afternoon (12:00 -14:00 pm), and in the evening (19:00- 21:00 pm). Additionally, to evaluate if the foraging period correlates with species' critical thermal limits (CTmax and CTmin), thermal tolerance was determined using a dry bath equipment. Finally, the trophic niche was determined through isotopic signature (δ 15N) using stable isotope analysis. The results of this study indicate habitat preference for all species except E. edentatum, which occurred at similar frequency in all sampled physiognomies. Regarding foraging periods, none of the species were found foraging exclusively during a single sampling period, with most being active at various times of the day. However, species with lower heat tolerance avoided foraging during the hottest times of the day, while species with higher thermal limits were most active during periods with higher temperatures. Additionally, we found high overlap in trophic positions, except for E. tuberculatum. Thus, although most Ectatomma species occupy the same trophic position, the overlap in the food niche appears to be mitigated by certain complementarities in other niche dimensions, which may help promote the coexistence of these species in the Cerrado. Therefore, this study reinforces the hypothesis of niche partitioning as a mechanism for the coexistence of ant species and provides valuable information about the natural history of the genus Ectatomma.